Molecular Peculiarities of Pro- and Eukaryotic Proteins Possessing Natural Adaptation to Low Temperatures - Gulevsky, Aleksandr K.; Tretiak, Diana V. (Problems of Cryobiology and Cryomedicine, 2015)
The review covers the findings in molecular modifications of proteins in cold-adapted organisms. According to the current data such modifications are attained via amino acid residue substitutions in a protein molecule, reduction of hydrogen bonds and salt bridges, hydrophobicity decrease. The specified modifications augment the flexibility of macromolecules thereby providing their functionality. The role of molecule-to-molecule interactions in protein stabilisation and their functional state within low temperature range is discussed. Probl Cryobiol Cryomed 2015; 25(3):219-234